Atrophic terrains: reviving Benoni's waterfront - Miles, Shanna (My University, 2018)
At the edge of an urban landscape there lies a dead space,forgotten and unloved. A place where nature slowly encapsulates and repossesses man-made structures. A slow urban decay where a previously active part of the city has now fallen into disrepair. This dying space consists of the urbanscape of the Benoni CBD, the parkscape of Dani Taljaard Park and the waterscape consisting of the Kleinfontein Dam. These atrophic terrains are in dire need of revival. Reflecting on Benoni’s history, we can learn from past atrophies to steer a course in creating a better urban environment for the future. Reactivating the space by bringing a diverse collection of people together to the area by creating attractive public places and offering both economic and social functions for a wide variety of users. A redevelopment needs to take place that is not only beneficial for the human, but also works in harmony with nature in order for both thrive on an equal footing. An intervention that not only aims to create a healthy space, but also to help the user have a healthier body and mind. Providing a mixed use of functions will attract more people to the space with a sports, recreation and rehabilitation centre as its main core. The facilities will provide for both land and water recreational activities. People will be encouraged to reengage with the water, offering facilities such as natural pools, waterplay and a nautical club. Indoor and outdoor sports courts, as well as smaller interventions such as running tracks and outdoor gyms along the periphery of the dam will promote physical activity. The intervention should be site sensitive, helping to rehabilitate the natural environment, specifically with regards to water. The pools will use a natural water purification process from storm water collection, that will be beneficial both economically and ecologically in the long run. It is not enough to simply create a new intervention in the hope of reactivating a space, one should also look at ways to create something that is socially, economically and ecologically sustainable in the long term. In a society with little money spent on maintaining a site, materials and technological solutions need to be chosen wisely in order to reduce the speed at which a place will decay or alternatively find ways to work with it, to find beauty in decay
A research report proposal submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Masters of Architecture (Professional). Date: 2018.02.09